SPATIAL DIVERSITY OF POVERTY IN POLAND - Ulman, Paweł; Wałęga, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Studies on poverty have a long tradition. In Poland, the issue acquired special significance with the beginning of the economic transition. Additionally, Poland’s accession to the European Union, particularly the need to implement the EU Strategy for Social Cohesion, imposed new requirements for the study of this phenomenon. The aim of the study is to assess the level and composition of poverty in the provincial system, and additionally, in cross-sectional of towns and villages in Poland and the identification of factors affecting the risk of poverty assuming different levels of the poverty line. In order to achieve these objectives, classical approach were used – based on the determining of the poverty line and the approach with the usage of a belonging function to the sphere of poverty based on the theory of fuzzy sets. In both cases, the monetary poverty is considered. Identification of potential factors affecting the risk of poverty was carried out using the logit model. To accomplish the purpose of the research an individual statistical data from the Central Statistical Office household budget survey in 2012 has been used.